2015
DOI: 10.1155/2015/827516
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Primary Open-Angle Glaucoma and Blood Pressure: Two Aspects of Hypertension and Hypotension

Abstract: Glaucoma is the second leading cause of blindness worldwide. Although the mechanism of the development of primary open-angle glaucoma (POAG) is not fully understood, elevated intraocular pressure (IOP) is considered the most important risk factor. Several vascular factors have also been identified as risk factors and can lead to hypoperfusion of the optic nerve head and thus may play an important role in the pathogenesis and progression of POAG. The results of the present study suggest that both high and low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 62 publications
2
36
0
1
Order By: Relevance
“…Emerging evidence has illustrated the positive association of elevated IOP with a number of predisposing factors or chronic diseases, including age [5], sex [6], blood pressure [7,8], genetic linkage [9], central corneal thickness [10], arterial stiffness [11], diabetes [12] and obesity [13]. Among these predisposing factors that affect the intraocular pressure, we focused more on the metabolic variables due to their association with many systemic diseases including cardiovascular disease and diabetes [14,15], which are curable via life style modification and medication.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has illustrated the positive association of elevated IOP with a number of predisposing factors or chronic diseases, including age [5], sex [6], blood pressure [7,8], genetic linkage [9], central corneal thickness [10], arterial stiffness [11], diabetes [12] and obesity [13]. Among these predisposing factors that affect the intraocular pressure, we focused more on the metabolic variables due to their association with many systemic diseases including cardiovascular disease and diabetes [14,15], which are curable via life style modification and medication.…”
Section: Introductionmentioning
confidence: 99%
“…IOP in subjects with BTM was low relative to controls, and was positively correlated with systolic blood pressure. High blood pressure is an important risk factor for IOP (6,9) hypertension causes excessive production of aqueous humor, increased episcleral venous and ciliary arterial pressures, and increased sympathetic activity leading to high IOP (18,19) . In a Taiwanese population, Lin et al, reported that of all the variables they measured, blood pressure was the strongest predictor of elevated IOP; this finding is supported by a recent epidemiologic study, as well as the correlation between IOP and systolic blood pressure described herein (20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive IOP is the most strongest and only treatable risk factor for developing glaucoma (4,5) . Additionally, excessive IOP has also been reported to be associated with other conditions such as diabetes, hypertension, obesity and metabolic syndromes (6)(7)(8)(9) . Metabolic syndromes and its components in turn, further exacerbate these conditions as it is strongly associated with insulin resistance, which plays a vital role in the development of diabetes, hypertension and obesity, and has been demonstrated in patients with BTM (12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…Þetta er í samraemi við aðrar rannsóknir sem hafa sýnt samband á milli haekkaðs blóðþrýstings og gláku. 15 Talið er að blóðþrýstingslaekkandi lyf geti minnkað blóðflaeði til sjóntaugar (reduced perfusion pressure) og þannig ýtt undir skemmdir á sjóntaug þeirra sem eru með gláku. 16 Það er því mikilvaegt að fylgjast vel með sjón og einkennum glákusjúklinga þegar blóðþrýstingsmeðferð er hafin.…”
Section: áHrif Meðferðar Annarra Sjúkdóma á Glákuunclassified